Predisposing factors, clinical features and treatment outcomes of Fusarium onychomycosis and comparison of its characteristics with Neoscytalidium onychomycosis - Sutasinee Phaitoonwattanakij (2022)
Background: Fusarium spp. are common organisms causing onychomycosis. Research on the clinical presentations and treatment of this condition is limited. Objective: This study evaluated the demographic data, clinical characteristics, and treatment outcomes of Fusarium onychomycosis. Methods: A retrospective study was conducted at Siriraj Hospital, Thailand. Patients with onychomycosis, at least 2 repeated positive mycological cultures for Fusarium spp., and a photo at diagnosis (January 2014–December 2019) were included. Demographic data and clinical characteristics of Fusarium onychomycosis were analyzed and compared with those of Neoscytalidium onychomycosis, the other common nondermatophytes onychomycosis in tropical countries. Results: Seventeen patients with twenty-four nails were analyzed. Fusarium onychomycosis was significantly related to a history of pedicure (p = 0.04). Predominant lateral involvements of subungual hyperkeratosis onychomycosis, but without concurrent foot infections, were significantly found in Fusarium onychomycosis (p < 0.001 for each). Among the treatments, urea was 80% effective. Topical amphotericin B was 75% effective. Both amorolfine 5% nail lacquer and long-pulsed 1064-nm neodymium:yttrium-aluminum-garnet laser were 66.7% effective. Lastly a combination of long-pulsed 1064-nm neodymium:yttrium-aluminum-garnet laser and amorolfine 5% nail lacquer was 50% effective. Conclusions: Important predisposing factors and clinical manifestations of Fusarium onychomycosis were a history of pedicure and predominant lateral-nail involvement, but no concomitant fungal foot infections. Topical treatment (urea cream, amphotericin B, or amorolfine nail lacquer) showed excellent outcomes.